Posthumous sperm retrieval: a procreative revolution - Francesca Negro; Renata Beck; Antonella Cotoia; Maria Cristina Varone (Medicinski glasnik, 2020)
Aim: Postmortem sperm retrieval with consequent artificial insemination has become a technically possible option for future use in assisted reproductive technology (ART). The authors have set out to discuss the social and ethical significance of posthumous sperm retrieval, and the laws currently in force in Italy, the United States and elsewhere. Methods: International literature from 1997 to 2020 has been reviewed from Pubmed database, Google Scholar and Scopus, drawn upon American, Italian and international sources (an ethically acceptable solution can only be achieved through an overhaul of the laws currently in effect). One of the most contentious issues was about donor consent. In Italy, a donor's will to retrieve his sperm in the event of premature disappearance can be proven according to the Law 219/2017, through advance health care directives. Results: A substantial increase, both in requests and protocols, was documented in the United States. In Italy, over the last two years, three rulings were issued concerning posthumous insemination. However, no official standardized protocols, guidelines or targeted legislation exist at the national level to regulate medical activity in that realm, whereas established laws often set implicit limitations. Conclusion: Current legal frameworks appear to be inadequate, because in most cases they were conceived under conditions that have radically changed. The need for newly-updated regulatory frameworks to promptly bridge that gap is increasingly clear, if current social needs related to reproductive rights are to be met in the foreseeable future.
Keywords: ART; Ethics; gamete supply; posthumous reproduction; posthumous sperm use